THE ROLE OF THE MOBILIZING TEACHER IN IMPROVING THE EQUALIZATION OF THE QUALITY OF TEACHER PERFORMANCE AT SD NEGERI 80 MALUKU TENGAH, BANDA SUB-DISTRICT - Yusuf, Ruliati; Djaja, Eka Sumandary (Faculty of Administrative Science, Universitas Brawijaya, 2025)
Indonesia is one of the countries that applies the paradigm in independent learning education through the driving teacher1 . In independent learning, a driving teacher is someone who is able to focus students in advancing themselves comprehensively in learning to develop themselves so that they can master critical thinking, and creative creativity. This study aims to analyze the role of the driving teacher in improving the equalization of the quality of teacher performance in Central Maluku State Elementary School 80. Analyzing the achievement of the Pancasila learning profile in students at SD Negeri 80 Maluku Tengah, Banda District. The approach used in this research is a qualitative descriptive approach, the data in this study were obtained by a series of interview activities with sources, observation and documentation. the research was conducted at SD Negeri 80 Maluku Tengah. The results of data analysis show that the driving teacher plays an important role in improving teacher performance and learning quality. By inviting teachers to collaborate and learn from each other, mobilizing teachers can help change the way teachers think and build their confidence. The results showed that in shaping the character of the Pancasila learner profile, it can be instilled through intraculricular activities and the Pancasila Learner Profile Strengthening Project (P5). Success in shaping the character of the Pancasila learner profile occurs if the teacher succeeds in implementing differentiated learning. The Education Unit has the flexibility in developing learning plans by referring to phases or learning outcomes that match the characteristics of students. P5 activities carried out at SD Negeri 80 Maluku Tengah succeeded in instilling the characters of critical thinking, mutual cooperation and independence on the theme of sustainable lifestyles. Good collaboration between principals, teachers, students, parents, and the community is one of the supporting factors in the successful implementation of the independent curriculum.